2023
DOI: 10.1001/jamanetworkopen.2023.5875
|View full text |Cite
|
Sign up to set email alerts
|

Historical Redlining, Social Determinants of Health, and Stroke Prevalence in Communities in New York City

Abstract: ImportanceHistorical redlining was a discriminatory housing policy that placed financial services beyond the reach of residents in inner-city communities. The extent of the impact of this discriminatory policy on contemporary health outcomes remains to be elucidated.ObjectiveTo evaluate the associations among historical redlining, social determinants of health (SDOH), and contemporary community-level stroke prevalence in New York City.Design, Setting, and ParticipantsAn ecological, retrospective, cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Of the 36 included articles, 31 (86%) found a significant association between worse redlining scores (i.e., HOLC grade C or D) and adverse health outcomes. More specifically, living in a redlined neighborhood, compared to neighborhoods with better redlining scores (i.e., HOLC grade A or B), was associated with more severe asthma (Friedman et al., 2022; Nardone, Casey et al., 2020; Schuyler & Wenzel, 2022), increased preterm birth rates (Hollenbach et al., 2021; Krieger, Van Wye et al., 2020; Nardone, Casey et al., 2020), increased late‐stage cancer diagnoses (Krieger, Wright et al., 2020), poorer breast cancer outcomes (Bikomeye et al., 2023), increased prevalence of cardiovascular disease or events (Al‐Kindi et al., 2023; Deo et al., 2023; Jadow et al., 2023; Motairek et al., 2022; White et al., 2021; Wing et al., 2022), increased COVID‐19 infection and death rates (Li & Yuan, 2022), poorer diabetes outcomes (Linde et al., 2022; White et al., 2021), increased gunshot wounds rates (Benns et al., 2020; Jacoby et al., 2018; Mehranbod et al., 2022; Spitzer et al., 2023), increased heat‐related illness rates (Li et al., 2021), increased infant mortality (Huang & Sehgal, 2022; Lynch et al., 2021), increased kidney failure rates (Nguyen et al., 2023), more childhood obesity (Kowalski et al., 2023), increased pedestrian fatalities (Taylor et al., 2023), increase in fatal encounters with police (Mitchell & Chihaya, 2022), worse postoperative outcomes (Diaz et al., 2021), increased maternal mortality (Gao et al., 2022), overall worse self‐rated physical health (Lynch et al., 2021; McClure et al., 2019), poorer mental health (Lynch et al., 2021), and increased prevalence of visual impairment and blindness (Hicks et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 36 included articles, 31 (86%) found a significant association between worse redlining scores (i.e., HOLC grade C or D) and adverse health outcomes. More specifically, living in a redlined neighborhood, compared to neighborhoods with better redlining scores (i.e., HOLC grade A or B), was associated with more severe asthma (Friedman et al., 2022; Nardone, Casey et al., 2020; Schuyler & Wenzel, 2022), increased preterm birth rates (Hollenbach et al., 2021; Krieger, Van Wye et al., 2020; Nardone, Casey et al., 2020), increased late‐stage cancer diagnoses (Krieger, Wright et al., 2020), poorer breast cancer outcomes (Bikomeye et al., 2023), increased prevalence of cardiovascular disease or events (Al‐Kindi et al., 2023; Deo et al., 2023; Jadow et al., 2023; Motairek et al., 2022; White et al., 2021; Wing et al., 2022), increased COVID‐19 infection and death rates (Li & Yuan, 2022), poorer diabetes outcomes (Linde et al., 2022; White et al., 2021), increased gunshot wounds rates (Benns et al., 2020; Jacoby et al., 2018; Mehranbod et al., 2022; Spitzer et al., 2023), increased heat‐related illness rates (Li et al., 2021), increased infant mortality (Huang & Sehgal, 2022; Lynch et al., 2021), increased kidney failure rates (Nguyen et al., 2023), more childhood obesity (Kowalski et al., 2023), increased pedestrian fatalities (Taylor et al., 2023), increase in fatal encounters with police (Mitchell & Chihaya, 2022), worse postoperative outcomes (Diaz et al., 2021), increased maternal mortality (Gao et al., 2022), overall worse self‐rated physical health (Lynch et al., 2021; McClure et al., 2019), poorer mental health (Lynch et al., 2021), and increased prevalence of visual impairment and blindness (Hicks et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…There is an emerging body of literature focused on identifying the impact of redlining on current-day health. For instance, findings from recent studies suggest that redlining is associated with increased rates of strokes (Jadow et al, 2023) and a higher risk of death from breast cancer (Wright et al, 2022). Recent reviews reported on the associations between historic redlining and adverse health outcomes, but they covered articles published through March 2022 (Cross et al, 2023;Lee et al, 2022;Swope et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…46,47 However, it was reported that upstream of established social determinants of health, historical housing discrimination resulting from structural racism could contribute to the community's stroke risk. 48 Several studies have reported a higher stroke risk in women in the general population, 15,49 whereas others have shown that male people living with HIV are more susceptible to stroke occurrence than female people. 6,36 The observed discrepancies among studies can be attributed to age group effects or associations with stroke risk.…”
Section: Discussionmentioning
confidence: 99%
“…Social status determinants of health (Figure ) were shown to have an impact on stroke prevalence and care. Low education, low income, and living in a health care professional shortage area were associated with increased community-level stroke prevalence in a cross-sectional study of residents in New York City 17 and were critical drivers of the excess likelihood of uncontrolled blood pressure among Black versus White participants in the REGARDS study (Reasons for Geographic and Racial Differences in Stroke). 13 Unemployed and low-income patients with stroke had lower likelihood of receiving reperfusion therapies, even when only considering patients with timely hospital arrival.…”
mentioning
confidence: 99%
“…16 Similarly, historical redlining was associated with modern-day stroke prevalence in New York City independently of contemporary individual measures of socioeconomic status. 17 Data from the Black Women's Health Study suggested that Black women who experienced interpersonal racism had higher stroke incidence than those without prior experiences of racism, 18 thus establishing a direct link between interpersonal racism and stroke incidence later in life.…”
mentioning
confidence: 99%